Legal Politics of Mining Spatial Planning in Sumenep District: Maqāṣid Syarī'ah Overview - Muhammad Shohibul Itmam,; Munir, Sirajul; Santoso, Lukman; Taufikin,; Abdelmalek Aouich, (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2025)
This research aimed to show the dynamics of mining spatial planning law in Sumenep Regency, Madura, Indonesia and the relevance to Maqāṣid Syarī'ah as a pillar of Islamic law. In this context, qualitative analysis was used by collecting data through observation, interviews, and document review. The results showed that phosphate mining regulations in Sumenep Regency reflected sensitive dynamics using political law theory as an analytical tool and a socio-legal method, where economic interests, environmental sustainability, and community aspirations were in conflict. Additionally, legal politics in the formulation of Regional Regulations (Perda) based on maqâṣid achieved a balanced utilization of natural resources with respect to the protection of nature and humanity. In Islamic law, this perspective is consistent with the principles of rahmatan lil-'ālamīn and 'imārah al-arḍ since humans are stewards of the earth. This study makes an important academic contribution by integrating the principles of maqāṣid syarī‘ah into the analysis of mining spatial planning law at the local level. The findings of this study indicate that the formulation of regional regulations based on maqāṣid not only enables the protection of the environment and community rights but also strengthens the role of Islamic law as an ethical instrument in the equitable and sustainable management of natural resources.